ANALISIS FILOLOGIS DAN KONTEKS HISTORIS NASKAH PAGAR PANGULU BALANG (NO. INV. 07.143) KOLEKSI MUSEUM NEGERI SUMATERA UTARA - Patar Kristian Sihombing; Herlina Herlina; Asriaty R Purba (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the Pagar Pangulu Balang manuscript (Inventory No. 07.143), one of the significant collections at the North Sumatra State Museum, through philological and historical contextual approaches. The manuscript contains teachings, advice, and customary leadership structures that reflect the socio-political system of the Batak community in the past. The research employs a descriptive-qualitative method based on philological analysis, including inventory, physical description, transliteration, textual normalization, and the preparation of a critical standard edition. Additionally, the study explores the historical context of the manuscript’s origin and its function within traditional social structures. The results show that Pagar Pangulu Balang is not merely a historical document but also conveys social values, customary law, and local leadership ethics. Linguistically, the manuscript employs a variant of the Batak language with distinct lexical characteristics, rich in metaphors and traditional symbols. Historically, the manuscript functioned as a guide for village governance and the relationship between the pangulu balang (customary leaders) and the community. These findings highlight the importance of preserving local manuscripts as sources of cultural knowledge and collective identity in traditional societies of North Sumatra. This study is expected to serve as a foundation for further research in philology, cultural anthropology, and the preservation of Indonesian manuscript heritage